PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MURDER UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI HUKUM NEWTON DAN PENERAPANNYA DI KELAS X SMA TRI BHAKTI PEKANBARU - Sari, Fardila; ', Azhar; ', Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to describe and differentiate the cognitive learning result student between the implementation of cooperative learning type MURDER group with conventional learning group in the Newton’s law and its application. This type of research is a quasi-experimental, with a intact group comparison design. Population in this research is all of X classes with 90 students. Meanwhile the samples are 28 students in X1 as control class and 30 students in X2 as experiment class. The instrument of data in this research is a score cognitive performance test which consists of 15 multiple choice items. Analysis of the data in this study was a descriptive analysis that was used to determine the performance of the physics cognitive learning through the criteria of absorption and effectiveness of learning. The inferential analysis was used to differentiate a cognitive learning considerably using independent samples t-test. The analysis data shows: the average absorption of the experiment class is 75.10% of the higher in category, and declared effective learning efficiently. Meanwhile the average absorption of the control class 68.54%. Therefore, it can be concluded that implementation of cooperative learning type MURDER can be used as an alternative in the learning process in the classroom X SMA Tri Bhakti Pekanbaru.